DIFFERENT TYPES OF INSPIRATORY MUSCLE TRAINING PROVIDES BETTERMENT IN ALTERED PULMONARY FUNCTIONS IN UPPER THORACIC SPINAL CORD INJURIES (International Journal of Physiotherapy, 2016)
Background: Respiratory problems are usual in upper thoracic spinal cord injuries when compared to Lower thoracic spinal cord injuries. Generally there are frequent respiratory complications in the individuals with spinal cord injuries. The complications of the respiratory system are severe and more prevalent source of morbidity and mortality after the spinal cord injury due to the inefficient breathing capacity including inspiratory and expiratory abilities. The present study represents the inspiratory muscle training especially in upper thoracic spinal cord injury patients to assess the improvement in the pulmonary functions.Methods: Twenty five patients with the age between 25 -40 years with the upper spinal cord injuries were selected in the present study in order to assess the efficacy of the training. Several types of exercises were practiced including diaphragmatic breathing exercises, incentive spirometry, active cycle of breathing technique and weight training. COPD Conditions, Chest wall deformities, Hypertensive patients, Cardio vascular problems were excluded in the study.Results: The results from the study showed that significant changes were found in the patients treated with all the above mentioned techniques. Axillary level, nipple level, Xiphisternum levels were analysed and the results found to be significant after the treatment. Incentive spirometry and peak flow meter observations were also found to be significant when compare to the pretreatment.Conclusion: The present study conclude that the combined effect of incentive spriometry, diaphragmatic breathing exercises, and active cycle of breathing technique is more effective in improving the pulmonary functions in upper thoracic spinal cord injuries than single method efficiency.